The The Application of a family intervention model based on health education towards Patient's Diabetes Mellitus Type II Self-Care at the Oesapa Public Health Center, Kupang City - Cendradevi Nugroho, Febtian; Banase, Emiliandry F.T (Window of Health : Jurnal Kesehatan, 2023)
Diabetes Mellitus is a chronic metabolic disease, and the number of sufferers increases every year. The Province of East Nusa Tenggara also experienced an increase of 1.2% for ages >15 years of 0.86%. The Kupang City region has the highest number of diabetes mellitus cases in East Nusa Tenggara Province, i.e., 29,242 patients. The number of people with diabetes mellitus increased from 2016 to 2018 at the Oesapa Health Center from 125 to 200 people. According to the latest data in 2020, there are 461 diabetes patients. To prevent an increase in mortality due to this disease, diabetes mellitus patients are expected to have good self-care with the support of family care. This study aimed to analyze the application of the Family Intervention Model to Self-care of Type II Diabetes Mellitus Patient's Health Education Based. A total of 80 respondents participated in filling out the Diabetes Self-Care Activity questionnaire. This research design is a queasy experiment. The data analysis used was the Paired T-Test with the result that there was an effect of the Application of the Family Intervention Model on Self-care of Type II Diabetes Mellitus Patients Based on Health Education with an α value of 0.000. This study concludes that providing health education through media books to families affects family intervention in patients so that they can improve self-care in patients with type II diabetes mellitus. Health workers should provide health education through book media to strengthen the Family Intervention Model for the care of Type II Diabetes Mellitus Patients.